Quantifying the health needs of migrants in vulnerable circumstances registered with a nurse-led primary care service. (May 2022) - Clark, Emily; Fox, Hannah; Gillam, Tara B; Clarry, Clodagh
Background: As of the end of 2019, at least 79.5 million people worldwide have been forced to flee their homes. Those seeking asylum face adversity before, during and after arrival in the UK, resulting in complex health and social needs. The study setting was a nurse-led asylum seeker service in a dispersal city, commissioned to provide an initial health assessment, immunisations and support to register with a general practitioner. Aims: The aim was to quantify the health needs of migrants in vulnerable circumstances registered with a nurse-led primary care service by clinical audit. Methods: In June 2018, 80 electronic records were reviewed by seven auditors to analyse documentation of demographics, asylum status, service use, barriers to care, physical and mental health. Results: Where data were available, 86% migrated due to persecution or trafficking, 59% had a chronic physical illness, 51% had a mental health condition and 49% experienced barriers to accessing a mainstream general practitioner. Conclusions: Although a small sample, this survey demonstrated high physical and mental health needs that are often unmet in mainstream services. There was a high level of unknown need, for example of torture rates. These findings informed quality improvement in documentation and health assessments, and further research.